Efectos de aprendizaje cooperativo en la organización de clases en estudiantes de secundaria en la Institución Educativa Nuevo Triunfo Loreto 2022 - Pizango Tangoa, Rusber Martin (2023)
The present study sought to determine the effect of Cooperative Learning on Classroom Organization, for which a pre-experimental type experimental research was developed, where a pre-test and a post-test were conducted with a population of 60 students of the Educational Institution "Nuevo Triunfo" - Loreto in the year 2022, in this way an initial observation was made to evaluate the organization of classes identifying the important points that should be improved to be able to apply the use of collaborative learning, After this period, an observation was made again to be able to qualify how the organization of classes was, which gave a positive result, since at the beginning it was found that most of the students had a low qualification, but in the final evaluation they obtained a qualification of medium, which indicates that there was a change in the independent variable. These verifications were made by means of the survey and direct observation techniques, being the instruments the questionnaire and the observation sheet that served in the pre-test and post-test, in such a way that as a final result it could be confirmed that there is an effect of Cooperative Learning in the Class Organization, and that this could be seen much better when cooperative learning is applied for a longer period of time.